Effects of firing temperature on the physical properties of a bauxite-based refractory castable - Goegtas, C.; Unlu, N.; Odabasi, A.; Sezer, L.; Guner, S.; Goller, G.; Eruslu, M. N. (Consultants Bureau/Springer, 2012)
A self-flowing low-cement bauxite castable was prepared from 64 wt.% rotary Chinese bauxite and 10 wt.% Eczacibasi calcined alumina aggregates with additives of 5 wt.% Lafarge cement Secar 71, 8 wt.% Elkem microsilica 971U, and 0.05 wt.% dispersant Darvan 7S (D7S). Optimum self-leveling flowability was achieved using 5.6% water addition. As a function of the firing temperature, the physicomechanical and refractory properties of the self-flowing low-cement bauxite castable were characterized in terms of densification parameters such as apparent porosity (AP), bulk density (BD), water absorption (WA), and cold crushing strength (CCS). Phase analysis and microstructural-based evaluation were performed using x-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. The present bauxite-based refractory castable heat treated at 1500A degrees C for 2 h exhibited the following properties: AP 13%, BD 2.93 g/cm(3), WA 4.4%, and CCS 1365 kg/cm(2).
Keywords: firing; x-ray methods; mechanical properties; Al2O3; refractories